ANDE BACA COMPROMISE AS RITUAL COMPLEMENT ENCOUNTERING VARIOUS PROBLEMS (International Conference on Social and Islamic Studies, 2022)
Ande baca or the food will be read and prayed is a food set (offerings) which is a complement in tola bala ritual, thank giving ritual, etc held by Mandar society, in West Sulawesi. This food usually consists of; sokkol (lemang/ sticky rice), buras (lapat/ rice cooked with coconut milk), ketupat, boiled egg, chicken curry, cucur (made from fried rice flour and red sugar), various kinds of banana, etc. However, ande baca has changed in nowadays. It means, the people behavior have different in holding the ritual, they don’t prepare the various offering (ande baca) completely for another food alternative, untill the way to serve the ande baca. This paper tries to find out how the ande baca compromise faces the various problems, from social, culture, and surrounding sides. Applying the research methods; qualitative, discussion, documentation, interview, observation, and looking for information from the various additional literature such as books, journals, etc. The study of ande baca will be analyzed using Durkheim theory up to Turner which relate to ritual and social-politic. Finally, ande baca will be last when it has compromise with the change. The original ande baca will “alive” by permitting additional factor to be in, therefore, ritual in Mandar as tradition can be preserved.